Role of chitinase produced from Azospirillum brasiliense in degradation free and snail chitin in soil - Hala M. Radif; Shatha S. Hassan (World Journal of Experimental Biosciences, 2014)
Azospirillum brasiliense Aw-1 isolated from soil of plant roots was used for production of chitinase and degradation of soil and snail chitin. Soil contained chitin was treated with the bacterial cells and cell free extract (crude chitinase). The level of reducing sugars (as an indicator for chitin degradation) was measured. Significant increase in the reducing sugars was observed after treatment with chitinase (631.6 μg/ml) and bacterial cells (846.6 μg/ml) as compared with the control (305 μg/ml). Azospirillum brasiliense Aw-1 chitinase was used for treatment snail (chitin containing organism). This treatment caused many changes in snail shell and death the animal. These results showed that the possibility of using the chitinase to overcome the ability of chitin containing organisms to cause the infection.
Keywords: Azospirillum brasiliense, Chitinase, Reducing sugars, Snail.